Burnout and Cardiovascular Risk in Healthcare Professionals During the COVID-19 Pandemic - Alameri, Fayeza; Aldaheri, Noura; Almesmari, Sarah; Basaloum, Manea; Albeshr, Nouf Albdulrahman; Simsekler, Mecit Can Emre; Ugwuoke, Nnamdi Valbosco; Dalkilinc, Murat; Al Qubaisi, Mai; Campos, Luciana Aparecida; Almahmeed, Wael; Alefishat, Eman; et al. (Frontiers in Psychiatry, 2022)
Introduction: The objective of this study was to investigate the psychosocial and cardiovascular markers in healthcare professionals during the COVID-19 pandemic. Methods: This was a STROBE compliant, blended exploratory study. Residents, staff physicians, nurses, and auxiliary healthcare professionals from both inpatient and outpatient medicine services were recruited using a planned random probability sample. The Maslach Burnout Inventory, Fuster-BEWAT score (FBS), and socio-demographic factors, as well as sleep quality, were studied. The correlations between burnout severity and cardiovascular risk were examined using multivariable linear regression models adjusted for confounding variables, such as sociodemographic and anthropometric characteristics. Results: The regression analysis with FBS as the outcome showed a negative association between cardiovascular health and emotional exhaustion [Coef.(95%CI): -0.029(-0.048, -0.01), p = 0.002]. The higher the emotional exhaustion the lower the cardiovascular health. Further, the model showed a positive association between personal accomplishment and cardiovascular health [Coef.(95%CI): 0.045(0.0007, 0.082), p = 0.02]. Emotional exhaustion was significantly positive correlated with REM sleep and light average (Spearman's rank correlation: 0.37 and 0.35, respectively, with P < 0.05). Discussion: This study suggests that healthcare practitioners with a lower composite cardiovascular health score may be at greater cardiovascular risk due to the concomitant emotional exhaustion. As an adaptive response to stressful situations, REM sleep increases. The findings of this study may be relevant in creating preventive strategies for burnout and cardiovascular risk reduction or prevention.